Missouri Homestead - Tedrow, Thomas L. (Nashville : T. Nelson, 1992)
In 1884, when Laura, Manly, and their daughter Rose come from South Dakota to Mansfield, Missouri, looking for a better life, Laura's outspoken articles against a local timberman cause some problems.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- Missouri -- Fiction; Missouri -- Fiction